RETRACTED: Critical Issues Facing SMEs’ Actors in the Adoption of Emerging Digital Marketing Technology (EDMT) - Sunday C. Eze; Vera C. Chinedu-Eze; Hart O. Awa; Sandra I. Diarah (SAGE Open)
This paper examines the ordeals actors of SMEs face in the adoption process of Emerging Digital Marketing Technology (EDMT). A conceptual framework was proposed to capture actors that participate in EMDT and the difficulties they (themselves) pose that hinder successful adoption. However, a purposive sample of 26 participants drawn from Crunch online database, Luton were interviewed on unstructured and semi-structured bases and analyzed using a thematic approach. The interviews on the problems were coded and classified based on the actors involved in the adoption process to extend the T-O-E framework. The findings revealed that while extant problems relate to the contexts of technology, organization, and environment, the extended T-O-E framework unraveled more critical problems that are linked to the in-grained human context. Implicit is that vendors should work on decision-makers, given that some of the adoption decisions are critically and continuously influenced by the actors.